Vapor-liquid equilibrium data for binary mixtures of acetic acid plus anisole, acetone plus anisole, and isopropanol plus anisole at pressure 96.15 kPa - Mali, Nilesh A.; Mali, Pawan K.; Patil, Asmita P.; Joshi, Sunil S. (Journal of Chemical and Engineering Data, 2017)
In this work, the vapor-liquid equilibrium (VLE) data have been generated at the local atmospheric pressure of 96.15 kPa for the binary systems acetic acid + anisole, acetone + anisole, and isopropanol + anisole. A circulation type apparatus was designed and developed with few modifications in one of the stills proposed in the literature. For the validation of the new apparatus, VLE data were generated for the known system of N,N-DMF + aniline and compared with the literature data. The VLE data, generated in Txy form for all pairs, were found to be consistent through the point-to-point consistency test. Activity coefficient models, Wilson, NRTL, and UNIQUAC, were fitted to these data using an objective function of minimizing the sum of deviation between experimental and calculated total pressures to estimate the binary interaction parameters. The model predictions with estimated parameters were compared with the experimental data and found appropriate.